Sistema de reprodução em pequenas populações fragmentadas e em árvores isoladas de Hymenaea stigonocarpa - De Moraes, Mario Luiz Teixeira [UNESP]; Kageyama, Paulo Yoshio; Sebbenn, Alexandre Magno (My University, 2007)
Six microsatellite loci were used to quantify the mating system of two small fragmented populations (Selviria - SEL and Aparecida do Tabuado - APT, Mato Grosso do Sul State) and isolated trees in pastures, of the bat-pollinated tropical tree Hymenaea stignocarpa, growing in the Center-west region of Brazil. In SEL population, seeds were collected from 11 mother-trees; in APT, from three trees and, in the case of isolated trees, from six individuals growing at least 500 m apart in pastures. To investigate if there are differences on mating system between trees in populations and isolated trees, trees from populations were pooled as a group and, likewise, the isolated trees were pooled to another group. The outcrossing rate was higher in the populations (t̂ m= 0.873) than in isolated trees (t̂ m=0.857), but the difference was not significant. Significant and high differences between multi-locus and single-locus outcrossing rate were detected in populations (t̂ m- t̂ s=0.301, P<0.05) and isolated trees (t̂ m- t̂ s=0.276, P<0.05), suggesting mating between relatives. Higher paternity correlation was observed in trees from population (r̂ p=0.636) than in isolated trees (r̂ p=0.377), indicating the occurrence of some correlated matings and that part of offspring are full-sibs. It was not observed increased in self-fertilization rate in isolated trees in pastures. In general terms, the unique observed difference in mating system between populations and isolate trees was the high rate of correlated matings in trees from populations, due probably to the small distance among coespecifics and the pollinator behavior, visiting near trees.
Mating system in small fragmented populations and isolated trees of Hymenaeo stigonocarpa
Keywords: Coancestry; Correlated matings; Effective population size; Inbreeding; Jatobá-do-cerrado; Tropical tree species; Mating system; Microsatellite loci; Fertilizers; Fungi; Seed; Forestry; Fertilization; Pollination; Seeds